Venezuela. Le gouvernement continue à recourir aux détentions arbitraires comme outil de contrôle et de répression - Amnesty International (Amnesty International, 2023)
Venezuela. Le gouvernement continue à recourir aux détentions arbitraires comme outil de contrôle et de répression. Dans le nouveau rapport intitulé Vidas detenidas: Continúan las detenciones arbitrarias por motivos políticos en Venezuela, Amnesty International dénonce la persistance de la politique de répression mise en œuvre par le gouvernement de Nicolás Maduro.
Venezuela, Bolivarian Republic of
Keywords: 2023-08 August

Les familles doivent avoir le droit de commémorer le 1er anniversaire de la mort de leurs proches tués lors du soulèvement, sans subir de représailles - Amnesty International (Amnesty International, 2023)
Dans ses nouvelles recherches, Amnesty International explique que les autorités iraniennes soumettent les familles des victimes à des arrestations et détentions arbitraires, restreignent indûment les rassemblements pacifiques sur les lieux d’inhumation et détruisent les pierres tombales.
Iran, Islamic Republic of
Keywords: 2023-08 August

Respect families’ right to commemorate loved ones killed during uprising without reprisals on one-year anniversary - Amnesty International (Amnesty International, 2023)
In new research, Amnesty International details how the Iranian authorities have been subjecting victims’ families to arbitrary arrest and detention, imposing cruel restrictions on peaceful gatherings at grave sites, and destroying victims’ gravestones.
Iran, Islamic Republic of
Keywords: 2023-08 August

Ukraine: Russian court upholds 13-year sentence against Ukrainian human rights defender Maksym Butkevych - Amnesty International (Amnesty International, 2023)
An appeal hearing at a Moscow court on Tuesday (22 August) which has upheld the 13-year sentence imposed on Maksym Butkevych, a Ukrainian human rights defender, is a grave miscarriage of justice Amnesty International said today.
Ukraine
Keywords: 2023-08 August; Russia

« La mort a frappé à notre porte ». Crimes de guerre et souffrances des populations civiles au Soudan - Amnesty International (Amnesty International, 2023)
Soudan. Généralisation des crimes de guerre avec des attaques aveugles et aussi délibérées contre la population civile – publication d’un nouveau rapport
Sudan
Keywords: 2023-08 August

Arbitrary detentions continue in Venezuela - Amnesty International (Amnesty International, 2023)
Venezuela: Arbitrary detentions continue as a tool of government control and repression. In the new report, Life detained: Politically motivated arbitrary detentions continue in Venezuela Amnesty International denounces the Nicolás Maduro.
Venezuela, Bolivarian Republic of
Keywords: 2023-08 August

Countries must safeguard children’s rights from climate change and environmental damage - UN committee - Amnesty International (Amnesty International, 2023)
UN Committee on the Rights of the Child has concluded that countries must urgently implement measures to address the damage and threat to children’s rights from climate change and environmental degradation.
Worldwide
Keywords: 2023-08 August; Child Rights

Crise climatique. Les États doivent protéger les droits des enfants du changement climatique et des dégradations de l’environnement - Comité des Nations unies - Amnesty International (Amnesty International, 2023)
Les enfants sont parmi les personnes les plus vulnérables aux conséquences du changement climatique et des dégradations de l’environnement dans le monde.
Worldwide
Keywords: 2023-08 August

Lebanon: Comedian Arrested for Critical Jokes - Amnesty International (Amnesty International, 2023)
Lebanese authorities’ arrest and investigation of prominent comedian Nour Hajjar, solely in retaliation for his jokes, represents a new escalation in Lebanon’s crackdown on public criticism, the Coalition to Defend Freedom of Expression in Lebanon of which Amnesty International is a member, said today.
Lebanon
Keywords: 2023-08 August

Ugandan authorities must drop charges in death penalty case under Anti-Homosexuality Act - Amnesty International (Amnesty International, 2023)
It is deeply disturbing that the Ugandan authorities are prosecuting people based on their real or perceived sexual orientation or gender identity.
Uganda
Keywords: 2023-08 August

“Death came to our home”. War crimes and civilian suffering in Sudan - Amnesty International (Amnesty International, 2023)
Sudan: War crimes rampant as civilians killed in both deliberate and indiscriminate attacks. Read the Report
Sudan
Keywords: 2023-08 August